Interrogando a ciência: a concepção vidaliana da geografia - Guilherme Ribeiro (Confins)
This article has as objective to join together the French geographer Paul Vidal de la Blache’s (1845-1918) theoretic and metodological reflections in order to support the existence of a true “vidalian” epistemology. We intend here a reading different from the usual, where Vidal de la Blache has been presented as an essentially descriptive and regional author. His interdisciplinary dialog, the description and the game on scales reveal us the complexity of his thought